2009
DOI: 10.1016/j.cell.2009.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Assembly Chaperones Govern Biogenesis of the Proteasome Regulatory Particle Base

Abstract: Summary The central protease of eukaryotes, the 26S proteasome, has a 20S proteolytic core particle (CP) and an attached 19S regulatory particle (RP). The RP is further subdivided into lid and base subcomplexes. Little is known about RP assembly. Here we show that four conserved assembly factors govern biogenesis of the yeast RP base. Nas2 forms a complex with the Rpt4 and Rpt5 ATPases and enhances 26S proteasome formation in vivo and in vitro. Other RP subcomplexes contain Hsm3, which is related to mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
237
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(262 citation statements)
references
References 39 publications
19
237
1
3
Order By: Relevance
“…Our FCS analysis did not detect proteasome assembly intermediates in wild-type cells, probably because such intermediates are not abundant [37][38][39][40] . Previous studies using a specific importin-a mutant, srp1-49, suggested that nucleocytoplasmic transport mediated by importin a/b is coupled to proteasome biogenesis [19][20][21]23 .…”
Section: Resultsmentioning
confidence: 62%
“…Our FCS analysis did not detect proteasome assembly intermediates in wild-type cells, probably because such intermediates are not abundant [37][38][39][40] . Previous studies using a specific importin-a mutant, srp1-49, suggested that nucleocytoplasmic transport mediated by importin a/b is coupled to proteasome biogenesis [19][20][21]23 .…”
Section: Resultsmentioning
confidence: 62%
“…Two competing models exist for RP assembly ( Funakoshi et al , 2009; Le Tallec et al , 2009; Park et al , 2009; Roelofs et al , 2009). The first posits that RP assembly occurs in modules independent of the CP with the help of four RP-dedicated chaperones, named Hsm3, Nas2, Nas6 and Rpn14 ( Funakoshi et al , 2009).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…The first posits that RP assembly occurs in modules independent of the CP with the help of four RP-dedicated chaperones, named Hsm3, Nas2, Nas6 and Rpn14 ( Funakoshi et al , 2009). In contrast, the second model proposes that the CP serves as a scaffold for the heterohexameric ATPase ring of the RP base ( Park et al , 2009).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…Like the CP assembly pathway, the base assembly is also a highly organized process assisted by four base-dedicated chaperone proteins, including Nas2/p27, Nas6/gankyrin = p28, Rpn14/PAAF1, and Hsm3/S5b (yeast/human: miscellaneous nomenclature) (Funakoshi et al , 2009 ;Kaneko et al , 2009 ;Le Tallec et al , 2009 ;Park et al , 2009 ;Roelofs et al , 2009 ;Saeki et al , 2009 ). Recent studies proposed renaming of Rpn14, Nas6, Nas2, and Hsm3, to RP assembling chaperones (RACs), i.e., RAC1, 2, 3, and 4, respectively (Tomko and Hochstrasser , 2011 ).…”
Section: Deubiquitylating Enzymesmentioning
confidence: 99%